Numerical investigation of ventilation performance in an impinging jet system with high-level placement - Chen Wang; Huifan Zheng; Yin Liu; Ke Hu; Xu Yan (Case Studies in Thermal Engineering)
The indoor ventilation performance of an impinging jet ventilation (IJV) system with high-level placement in non-occupied zone was comprehensively investigated using numerical simulation methods. Combined with response surface methodology (RSM), the differences in thermal comfort and energy efficiency between high-level and low-level placements were quantified for different seasonal conditions. The results indicate that in summer, thermal buoyancy resistance is relatively low, and buoyancy facilitates the accumulation of cool air in the occupied zone, forming a comfortable ventilation environment. Minimal differences were observed between the ventilation environments induced by high-level and low-level air supply placements. Conversely, in winter, the warm airflow from the supply is significantly affected by buoyancy, often rising prematurely unless delivered with high inertial force, in which case high-level placement can achieve performance comparable to low-level placement. The quantitative analysis using RSM revealed that in summer, the thermal comfort and energy efficiency of both high-level and low-level placements were nearly equivalent, with high-level placement slightly outperforming in terms of thermal comfort, while low-level placement demonstrated marginally better energy efficiency. In winter, low-level placement exhibited clear advantages in heating ventilation performance. This study provides theoretical support for the efficient design of IJV systems.